Validation of the International Prognostic Scoring System (IPSS) for Waldenstrom's Macroglobulinemia (WM) and the importance of serum lactate dehydrogenase (LDH) - Kastritis, E.; Kyrtsonis, M.-C.; Hadjiharissi, E.; Symeonidis, A.; Michalis, E.; Repoussis, P.; Tsatalas, C.; Michael, M.; Sioni, A.; Kartasis, Z.; Stefanoudaki, E.; Voulgarelis, M.; et al. (Leukemia Research, 2010)
The recently proposed, ISSWM staging system for symptomatic patients with WM was based on patients treated with alkylating agents and nucleoside analogs and has not been externally validated nor has been validated for cause-specific survival (CSS). We independently validated ISSWM both for overall survival (OS) and for CSS and assessed whether addition of elevated serum LDH may add to the strength of ISSWM in 335 patients treated upfront mainly with alkylating agents (43%), and rituximab-based therapies (47%). ISSWM could discriminate three groups with significantly different OS and CSS (p< 0.01 for both). High serum LDH was predictive of shorter OS and CSS (p< 0.01). The combination of high risk according to ISSWM and elevated serum LDH identified a subset of patients for whom innovative treatment approaches are needed. © 2010 Elsevier Ltd.
Keywords: age; Cause-specific survival; High risk; Lymphoplasmatic lymphoma; Prognosis